Análisis de factibilidad para la compensación de reactivo en función del mínimo de pérdidas en redes de distribución - Clavijo Flores, Fabricio German (2015)
This draft thesis develops to modeling Allows to study the behavior of the power grid before the installation of capacitor banks in it. The aim of Implementing compensation equipment in the network 's main function is Reducing energy losses in the network, the Presence of These energy losses Directly Affect the quality of energy That Is Being delivered to the end customer or subscriber. To meet the objective of Minimizing energy losses have created a model of location and proper sizing of capacitor banks in MATLAB, so it is Proposed to Provide an energy efficiency scenario Where the energy reaching the end consumer is Consumed responsibly and efficiently, resulting in a better voltage profile in networks and energy savings Because of loss minimization